Education Report 1959 of Committee on General Education - Trinidad and Tobago. Committee on General Education (Government Printery, 1959)
The Committee on General Education in Trinidad and Tobago was set up in July 1957 with the following terms of reference: “To consider the operation of the educational system of the country and make recommendations for future policy related to the curriculum, the improvement of academic and other standards, and the integration of the diverse elements which comprise of our population. “ The report is presented in the following sections: 1) A historical survey of primary and secondary education, 2) Responsibility and control, 3) The school system, 4) Adult education, 5) The teaching profession, 6) School buildings, 7) Tobago, 8) Miscellaneous, 9) Finance, 10) Recommendations, and 11) Proposals for new education ordinance.
Chairman: J. Hamilton Maurice
Keywords: General education